Paul Eluard: Yugoslavian Episode - Mladenović, Velimir (Literatūra, 2020)
The paper discusses the personal and political relations between the French surrealist poet Paul Éluard and Serbian writers and intellectuals, first of all Marko Ristić, a theorist and one of the founders of the Serbian surrealist movement. We will show the reception of Éluard’s works in the Serbian cultural space, his visit to Yugoslavia, then Éluard’s activities in Paris related to Yugoslav politics. One significant part of the article represents, until now, unpublished archival documents that testify to the friendship between Éluard and Ristić. We will try to explain how this friendship ended after the Cominform Resolution in 1948 and what consequences it had on Serbian and French culture.
Keywords: Paul Éluard; Marko Ristić; surrealism; reception